2016
DOI: 10.1097/md.0000000000005428
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique for laparoscopic harvesting of latissimus dorsi flap with prosthesis implantation for breast reconstruction

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Endoscopic non-robotic LDFR was reported in several studies [4][5][6][7][8], and in 2007, Missana et al reported a study including 52 patients [4] and more recently by others with smaller series [6][7][8]. Nakajima et al [8] reported a study with 168 LDF video-assisted reconstructions but only for reconstruction after partial mastectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic non-robotic LDFR was reported in several studies [4][5][6][7][8], and in 2007, Missana et al reported a study including 52 patients [4] and more recently by others with smaller series [6][7][8]. Nakajima et al [8] reported a study with 168 LDF video-assisted reconstructions but only for reconstruction after partial mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Development of robotic surgery since several years was very important for prostatic cancer, gynecologic cancer, colo-rectal cancer, and thoracic and thyroid surgery [1][2][3]. Endoscopic non-robotic latissimus dorsi-flap breast reconstruction (LDFR) has been reported in several studies [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in our institution, we performed endoscopic harvesting of latissimus dorsi flap with prosthesis implantation for immediate breast reconstruction after nipple-sparing mastectomy in 2 patients with breast cancer who wished to avoid a long scar on the back. Both patients were satisfied with the esthetic results of the procedure using only 3 small trocar ports instead of a long visible scar on the back [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although this method is designed to cover the surgical scar on the bra line at the back, the inevitable presence of long scars remains a disadvantage. To compensate for this drawback, a method of transferring and applying an LD muscle flap to the mid-axillary line has been developed [ 36 37 ]. Using the latest devices (endoscopy-assisted or robotic-assisted methods), total breast reconstruction is possible by transferring only the LD muscle flap through a smaller incision using the one-port incision method to approach the mid-axillary line ( Figure 9 ).…”
Section: Breast Reconstruction After “Aesthetic Scar-less” Nipple-spamentioning
confidence: 99%